2021
DOI: 10.3390/vaccines9111367
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Spike SARS-CoV-2 IgG Assessment with a Commercial Assay during a 4-Month Course after COVID-19 Vaccination

Abstract: We intended to assess the humoral response induced by the Pfizer/BioNTech Comirnaty COVID-19 vaccine with commercially available immunoassays: anti-spike (S) IgG and IgM, and anti-nucleocapsid (N) IgG antibodies, over a 4-month course. One hundred subjects, including 15 COVID-19 convalescents, comprised the study cohort. The SARS-CoV-2 antibodies concentrations were measured on day 0′ and 10′, 20′, 30′, 60′, 90′, and 120′ after the first dose administration. Over the course of the study, 100% of the participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…On the contrary, the presence of liver disease or liver cirrhosis showed no correlation with antibody titers or neutralizing activity. Regarding age, our findings are consistent with previously published data on the effect of age on both immunogenicity and subsequent sustainability of humoral responses [25][26][27][28]. This could be partially explained by immunosenescence along with enriched comorbidities in older individuals [29].…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, the presence of liver disease or liver cirrhosis showed no correlation with antibody titers or neutralizing activity. Regarding age, our findings are consistent with previously published data on the effect of age on both immunogenicity and subsequent sustainability of humoral responses [25][26][27][28]. This could be partially explained by immunosenescence along with enriched comorbidities in older individuals [29].…”
Section: Discussionsupporting
confidence: 91%
“…Further improvements focused on antibody specificity [ 10 , 11 , 12 ]. This is particularly important, considering that only the assays based on SARS-CoV-2 spike (S) protein are able to detect the humoral response to the vaccination [ 13 ]. Nucleocapsid-based (N, NCP) kits are not widely used in the vaccination era.…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Swadźba et al [11] on the humoral response induced by the Pfizer/BioNTech Comirnaty COVID-19 vaccine reported that the concentration of antibodies significantly decreased between days 90 and 120.…”
Section: Discussionmentioning
confidence: 99%